2011
DOI: 10.21273/jashs.136.3.198
|View full text |Cite
|
Sign up to set email alerts
|

Production of Haploids in Persian Walnut through Parthenogenesis Induced by Gamma-irradiated Pollen

Abstract: We report the first successful regeneration of haploid lines in persian walnut (Juglans regia) developed by in situ parthenogenesis followed by embryo rescue. Female flowers of cultivars Hartley and Pedro and two native Iranian selections (Z63 and Z67) were pollinated using pollen of selections Z53 and Z30 that had been irradiated with gamma rays at five doses (50, 150, 300, 600, and 900 Gy). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…All here presented data, which derive from the surveyed studies, were reconsidered and collectively standardized, and thus they are here comparatively indicated as percentage of their respective untreated controls (Tables 1, 2, & 3). In summary, IR caused a suppression of pollen germination (Table 1) and tube growth (Table 2) in a dose‐dependent manner (Cuny et al, 1993; Kumar & Rai, 2006; Peixe et al, 2000; Pfahler, 1971; Sadat Hosseini Grouh et al, 2011; Todorova et al, 2004; Zhang & Lespinasse, 1991; Zottini et al, 1997). Compared to the extensively performed rather low dose research on human and animal cells, the artificially applied radiation doses on pollen were very high and the results clearly demonstrate that pollen performance withstands much higher radiation levels.…”
Section: High Dose Ir‐effects On Pollen Germination and Tube Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…All here presented data, which derive from the surveyed studies, were reconsidered and collectively standardized, and thus they are here comparatively indicated as percentage of their respective untreated controls (Tables 1, 2, & 3). In summary, IR caused a suppression of pollen germination (Table 1) and tube growth (Table 2) in a dose‐dependent manner (Cuny et al, 1993; Kumar & Rai, 2006; Peixe et al, 2000; Pfahler, 1971; Sadat Hosseini Grouh et al, 2011; Todorova et al, 2004; Zhang & Lespinasse, 1991; Zottini et al, 1997). Compared to the extensively performed rather low dose research on human and animal cells, the artificially applied radiation doses on pollen were very high and the results clearly demonstrate that pollen performance withstands much higher radiation levels.…”
Section: High Dose Ir‐effects On Pollen Germination and Tube Growthmentioning
confidence: 99%
“…Most experiments studying the effects of ionizing radiation on pollen germination and tube growth were performed in breeding programs or classical genetic studies utilizing acute high doses of gamma irradiation on mature pollen of culture plants to induce haploidy by artificial parthenogenesis (Aleza et al, 2009; Blasco, Badenes, & Del Mar Naval, 2016; Bouvier, Zhang, & Lespinasse, 1993; Lecuyer, Zhang, Tellier, & Lespinasse, 1991; Peixe, Campos, Cavaleiro, Barroso, & Pais, 2000; Todorova, Ivanov, Nenova, & Encheva, 2004; Zhang & Lespinasse, 1991). Since Blakeslee et al, (1922) first reported that pollination with irradiated pollen induces in situ haploid plants of Jimson Weed, this has become a widely used technique which has been applied to produce parthenogenetic seeds of several crop plants, such as apple (Zhang & Lespinasse, 1991), citrus (Aleza et al, 2009), kiwifruit (Pandey, Przywara, & Sanders, 1999), loquat (Blasco et al, 2016), muskmelon (Cuny, Grotte, Dumas de Vaulx, & Rieu, 1993), pear (Bouvier et al, 1993), rose (Meynet, Barrade, Duclos, & Siadous, 1994), winter squash (Kurtar, 2009; Kurtar & Balkaya, 2010), pumpkin (Kurtar, 2009; Kurtar, Balkaya, Ozbakir, & Ofluoglu, 2009), sun flower (Todorova et al, 2004), sweet cherry (Höfer & Grafe, 2003), walnut (Sadat Hosseini Grouh, Vahdati, Lotfi, Hassani, & Biranvand, 2011) and watermelon (Sari, Abak, Pitrat, Rode, & Dumas de Vaulx, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, analytical tools such as flow cytometry are a reliable and convenient method to estimate genome size of plant communities such as ornamental plants (Abedi et al, 2015), medicinal plants (Javadian et al, 2017;Mahdavi and Karimzadeh, 2010;Majdi et al, 2010;Sadat Noori et al, 2017;Tarkesh Esfahani et al, 2016;Tavan et al, 2015) and fruit trees such as peach (Baird et al, 1994), olive (Brito et al, 2008;Loureiro et al, 2007b), coconut (Freitas et al, 2015), and Malus species (Hofer and Meister, 2010;Korban et al, 2009;Podwyszy nska et al, 2016). Unlike other fruit trees and plant species, there has been no study on the genome size of different walnut genotypes and cultivars, only flow cytometry is used to determine the ploidy level of walnut samples in in vitro conditions with the aim of identifying haploid plants (Sadat Hosseini Grouh et al, 2011).…”
mentioning
confidence: 99%
“…Fixed root tips were placed in aceto-ironhematoxylin dye for staining chromosomes (Lu and Raju, 1970). The fixed root tips were hydrolyzed in 1 N HCl for 12 min at 60°C and squashed in a drop of 45% (v/v) acetic acid as outlined in our previous studies (Sadat Hosseini Grouh et al, 2011). Arm ratios, average lengths and relative lengths were calculated using Excel 2007 (Microsoft) using a sample size of five cells/observation.…”
Section: Methodsmentioning
confidence: 99%